Review of the family Vanhorniidae (Hymenoptera: Proctotrupoidea), with the description of two new species - Abe, Junta; Yamagishi, Kenzo; Konishi, Kazuhiko (Zootaxa, 2024)
World species of the genus Vanhornia, the only member of Vanhorniidae, are reviewed and six species are recognized. Two new species, V. formosana sp. nov. from Taiwan and V. hikosanensis sp. nov. from Japan, are described. The record of V. eucnemidarum from South Korea is invalidated. New distributional records are reported for V. quizhouensis from Laos and V. yurii from Japan and South Korea. A key to species of Vanhornia is provided with photographs of all species.